ANALISIS PENGARUH KEUNGGULAN PRODUK DAN KUALITAS PELAYANAN PADA KEPUASAN PELANGGAN TERHADAP MINAT MEREFERENSIKAN (Studi Pada Pelanggan Listrik Pra Bayar PT. PLN (Persero) APJ Semarang) 2008-2012 - Sari, Ratna Puspita; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
PT. PLN (Persero) is a service company in the field of employment-listrikan in Indonesia.  The  company  is a state-owned  entities  (SOEs),  which  served  to provide and distribute electrical energy to the community that contains a social mission with optimum service. The services company, has sought to improve the performance (performance) company optimally and efficiently, by increasing the ability  to  memahamui  changes  in  market  structure  and  is  able  to  choose  an effective marketing strategy through product excellence. This is done so that the PLN can give satisfaction to customers, so the reference interest could be better.The  purpose  of  this  research  is  to  analyze  the  influence  of  product excellence  and quality  of service  to customer  satisfaction  PLN  (Persero)  APJ Semarang, to analyze the effect of customer satisfaction on the reference interest PLN (Persero) APJ Semarang. The population in this study is the customer PT. PLN  (Persero)  APJ  Semarang,  with  a  total  sample  of  100  respondents.  The sampling technique was accidental sampling. The data used are primary data and secondary data questionnaire  with literature. The analysis tool used is multiple regression.The results of this study are: quality service and significant positive effect on  customer  satisfaction.  Product  excellence  and significant  positive  effect  on customer satisfaction. Customer satisfaction positive and significant effect on the interest reference.